Community Empowerment Through MSME Development of the Dompet Dhuafa Resilient Family Program in Seberang Ulu District in Palembang City - Rahmat Hidayatullah; Alfitri Alfitri; Ridhah Taqwa (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to explain community empowerment through the development of MSMEs in the Resilient Family Program managed by Dompet Dhuafa in Seberang Ulu II District, Palembang City. This study uses a qualitative method to examine the process and results of empowerment that occurs. The results of the study show that the collection of ZIS funds by Dompet Dhuafa South Sumatra has increased significantly every year over the past three years, from Rp. 3,578,217,860 in 2018, increased to Rp. 4,543,689,070 in 2019, and reached Rp. 6,278,525,186 in 2020. This increase reflects the increase in the number of underprivileged people receiving assistance, as well as efforts to better distribute the economy. Community empowerment through MSME development in this program includes three stages: awareness stage, capacity stage, and empowerment stage. The awareness stage faces the challenge of low public awareness of the importance of innovation in entrepreneurship. The capacity building stage provides entrepreneurial skills to business actors affected by the Covid-19 pandemic, improving their abilities in physical, social, and economic aspects. The empowerment stage makes independent business actors with the ability to manage their resources. Dompet Dhuafa conducts feasibility studies, determines the type of business, conducts guidance, and evaluations to ensure that the Tangguh Family Program is on target.